Aid to Africa: the resignation of politicians - (:unkn) unknown (My University, 1999)
In the aftermath of the reform of the institutions of French cooperation which took centre stage in 1998, three factors affecting the development of French aid to Africa are often seen as favourable: the negotiation of the successor agreement to the Lomé Convention, the Cologne Initiative on Debt and Aid Untying – a fourth factor, the post-war period in Kosovo, is clearer in the light of the international meetings in the summer of 1999. These factors combine to justify bleak prospects for the evolution of aid to Africa.Article originally published under pseudonym in Politique Africaine n°1999/3 (N° 75), pages 107 à 117
Keywords: African Research